2011
DOI: 10.1016/j.biopsych.2010.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Functional Magnetic Resonance Imaging Brain Activation in Bipolar Mania: Evidence for Disruption of the Ventrolateral Prefrontal-Amygdala Emotional Pathway

Abstract: Background Bipolar I disorder is defined by the occurrence of mania. The presence of mania, coupled with a course of illness characterized by waxing and waning of affective symptoms, suggests that bipolar disorder arises from dysfunction of neural systems that maintain emotional arousal and homeostasis. We used functional magnetic resonance imaging (fMRI) to study manic bipolar subjects as they performed a cognitive task designed to examine the ventrolateral prefrontal emotional arousal network. Methods We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
116
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 132 publications
(131 citation statements)
references
References 44 publications
12
116
2
1
Order By: Relevance
“…Specifically, regression analyses were performed for PARS score and BOLD signal (in response to emotional images) in regions of interest (ROIs) based on regions in which significant treatment-related differences were observed in the more conservative voxelwise analysis. The ROI activation in response to emotional images was extracted from measurements obtained from the neuroanatomic scans using semiautomatic segmentation (gray and white matter) and volumetric analyses performed as previously described (Strakowski et al, 2011;Strawn et al 2012a). Findings were considered statistically significant at the p < 0.05 level.…”
Section: Fmri Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, regression analyses were performed for PARS score and BOLD signal (in response to emotional images) in regions of interest (ROIs) based on regions in which significant treatment-related differences were observed in the more conservative voxelwise analysis. The ROI activation in response to emotional images was extracted from measurements obtained from the neuroanatomic scans using semiautomatic segmentation (gray and white matter) and volumetric analyses performed as previously described (Strakowski et al, 2011;Strawn et al 2012a). Findings were considered statistically significant at the p < 0.05 level.…”
Section: Fmri Analysismentioning
confidence: 99%
“…These circuits, which modulate emotional and social behavior and, ultimately, maintain emotional homeostasis (Strakowski et al 2011), include the amygdala, medial prefrontal cortex (Brodmann area [BA] 10/ 11), rostral insula, subgenual/rostral anterior cingulate cortex (ACC) (BA 25, BA 24/32), ventrolateral prefrontal cortex (VLPFC) (BA 10/47), and dorsolateral prefrontal cortex, structures that are frequently implicated in pediatric anxiety disorders (Blackford and Pine 2012;Strawn et al 2012cStrawn et al , 2013Strawn et al , 2014b.…”
Section: Introductionmentioning
confidence: 99%
“…Emotional dysregulation in BD has also been linked to atypical functional hemispheric asymmetries as shown by neuroimaging studies (Yurgelun-Todd et al, 2000;Foland et al, 2008;Killgore et al, 2008;Strakowski et al, 2011;Liu et al, 2012) suggesting a deviation from the typical right hemisphere advantage in emotion perception. For example, Killgore et al, (2008) found a decrease in right inferior orbitofrontal activation in BD patients with manic symptoms during passive viewing of a series of black and white fearful facial expressions.…”
Section: Introductionmentioning
confidence: 96%
“…However, there were also two regions that had a stronger relationship between these imaging modalities in the bipolar versus healthy control group (i.e., coupling was enhanced), the left temporal pole and left inferior temporal gyrus. Many of these regions have been previously implicated by functional imaging studies as having a role in bipolar disorder (Cerullo, Adler, Delbello, & Strakowski, 2009; Gruber, Rogowska, & Yurgelun‐Todd, 2004; Keener & Phillips, 2007; Maletic & Raison, 2014; Strakowski et al., 2011; Townsend et al., 2012; Whitton, Treadway, & Pizzagalli, 2015; Yoshimura et al., 2014), which suggests that the altered relationship between fT1ρ and BOLD is related to the illness. For instance, numerous studies have shown that functional activity in the striatum is altered in bipolar disorder during the completion of reward tasks (Caseras, Lawrence, Murphy, Wise, & Phillips, 2013; Whitton et al., 2015; Yip, Worhunsky, Rogers, & Goodwin, 2014) and reduced during fear perception tasks (Killgore, Gruber, & Yurgelun‐Todd, 2008).…”
Section: Discussionmentioning
confidence: 99%